Assessing Efficiency of the European Banking Sectors: an Application of the Network DEA - Emília Zimková; Ľubomír Pintér (Statistika: Statistics and Economy Journal)
The global financial crisis, sovereign debt crisis, Covid-19, and the invasion in Ukraine highlighted the need to optimise the production processes in banking sectors in Europe. Data Development Analysis (DEA) is a method used to evaluate the efficiency of production units and to benchmark them. It is an important part of analysing and managing the production processes. The contribution attempts to measure and compare technical efficiency scores of 26 European banking systems in 2020 and 2021 by using Network-Data Envelpment Aanalysis (N-DEA), specifically the two-stage slacked-based model (SBM) by Kaoru Tone and Miki Tsutsui (2009). The methodology of NSBM-DEA allows us to assess the efficiency scores of two sub-processes: the deposit collection process and the intermediation process that reflects the use of deposits for earning assets (loans and purchased bonds). Therefore, by NSBM-DEA the deposit collection efficiency, the intermediation proces efficiency and its overall technical efficiency can be gained. Most banking systems in Europe reveal a large inefficiency in collection of deposits and higher efficiency in intermediation of the deposits into earning assets. Our findings show that in 2020 and 2021 only 2 out of 26 European banking sectors were technically efficient in the deposit collection phase, namely Latvia and Malta. In the intermediation phase, the only France was almost technicaly efficient (99.9% in 2020 and in 2021 as well). As to the overall technical efficiency, as the best overal efficiency was reached by the banking systems of France and Germany. The result of our contribution is benefitial to policymakers, regulators, or economists that must assess the performance of the entire banking sectors. The deeper integration of the banking sectors through initiatives like the BankingUnion is inevitable.